2001
DOI: 10.1614/0890-037x(2001)015[0122:cowmsi]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Weed Management Systems in Narrow-Row, Glyphosate- and Glufosinate-Resistant Soybean (Glycine max)1

Abstract: Field experiments were conducted near DeKalb and Urbana, IL, and Columbia, MO, in 1997 and 1998 to evaluate weed management systems in glyphosate- and glufosinate-resistant soybean planted in 18-cm rows. Overall weed control was improved to a greater extent when the rate of glufosinate was increased from 300 to 400 g ai/ha than when the rate of glyphosate increased from 630 to 840 g ae/ha. Sequential applications of glufosinate improved control over single applications, whereas sequential treatments of glyphos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(69 citation statements)
references
References 5 publications
4
65
0
Order By: Relevance
“…A similar response was observed with the AI nozzles, where there was an increase in weed control of 1-24% when glyphosate was applied at the manufacturer's full recommended dose compared to the half dose. Wiesbrook et al (2001) also found that glyphosate applied at 840 g ha -1 provided excellent control of Setaria faberi (giant foxtail), A. theophrasti, and C. album. There was no effect of the water carrier volume with the FF nozzles, but the AI nozzles with the 100 L ha -1 rate improved the control of A. theophrasti (4%) and P. persicaria (8%).This is consistent with the results of Knoche (1994), who found that, with glyphosate, herbicidal performance increased as the carrier volume decreased.…”
Section: Resultsmentioning
confidence: 89%
“…A similar response was observed with the AI nozzles, where there was an increase in weed control of 1-24% when glyphosate was applied at the manufacturer's full recommended dose compared to the half dose. Wiesbrook et al (2001) also found that glyphosate applied at 840 g ha -1 provided excellent control of Setaria faberi (giant foxtail), A. theophrasti, and C. album. There was no effect of the water carrier volume with the FF nozzles, but the AI nozzles with the 100 L ha -1 rate improved the control of A. theophrasti (4%) and P. persicaria (8%).This is consistent with the results of Knoche (1994), who found that, with glyphosate, herbicidal performance increased as the carrier volume decreased.…”
Section: Resultsmentioning
confidence: 89%
“…Sequential glyphosate treatments provided 89 to 100% weed control in both years and were more effective than the single treatment in 1998, supporting findings of Wait et al (1999) and Payne and Oliver (2000) that sequential treatments result in greater and more consistent weed control. Wiesbrook et al (2001), however, found that sequential treatments of glyphosate gave no advantages over single applications in weed control or soybean yield. The best option for growers would be to apply glyphosate at the second to third trifoliate stage and then scout fields and decide on the need of a second glyphosate treatment based on weed density and potential for yield loss due to late season competition.…”
Section: Soybean Yieldmentioning
confidence: 97%
“…Research in the USA has shown that weed control with glyphosate is affected more by rate than time of application (Ateh and Harvey 1999;Mulugeta and Boerboom 2000;Vangessel et al 2000;Krausz and Young 2001). Sequential applications have provided greater and more consistent weed control than have single applications (Wait et al 1999;Payne and Oliver 2000;Wiesbrook et al 2001). However, level of weed control was dependant on time of application of single treatments and on crop row width, with Abbreviations: CHU, corn heat unit 1199 greater control at narrow-row spacings (Ateh and Harvey 1999;Young et al 2001).…”
Section: Ivany J a 2004 Comparaison Des Méthodes De Lutte Contre mentioning
confidence: 99%
“…The use of soil-residual herbicides not only can increase the number of MOAs used in a herbicide program, but can also offer extended weed control compared to POST herbicides (i.e., glyphosate or glufosinate) that lack residual activity (Taylor-Lovell et al 2002;Wiesbrook et al 2001). The efficacy of soil-residual herbicides is highly dependent on either rainfall or irrigation shortly after application, which places the herbicide molecules into soil solution where they can be taken up as weeds germinate and emerge (Krausz et al 2001;Stewart et al 2010).…”
mentioning
confidence: 99%